Palladium-graphene hybrid as an electrocatalyst for hydrogen peroxide reduction - Čović, Jelena; Mirceski, Valentin; Zarubica, Aleksandra; Enke, Dirk; Carstens, Simon; Bojić, Aleksandar; Ranđelović, Marjan (Elsevier BV, 2022)
The electrocatalytic reduction of hydrogen peroxide in an alkaline solution has been studied on a hybrid material based on hydrothermally obtained palladium particles supported on graphene (Pd@G). The morphology, structure, and chemical composition of the prepared hybrid material, including spatial distribution of palladium nanoparticles, were examined by SEM, XRD, EDX, elemental mapping, XPS, FTIR, and BET. The hydrogen peroxide reduction reaction (HPRR) was studied by cyclic and square wave voltammetry in an oxygen-free and air-saturated alkaline medium. The Pd@G exhibited pronounced electrocatalytic activity for HPRR, which proceeds via complex electrode mechanisms coupled with adsorption phenomena and hydrogen peroxide disproportionation reaction as a heterogeneous chemical process on the surface of palladium nanoparticles.
Keywords: Hydrogen peroxide reduction reaction Electrocatalysis Hybrid material Palladium Graphene